2019
DOI: 10.3390/polym11050787
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene-Matrix Composites with Halloysite Nanotubes with Enhanced Physical/Thermal Properties

Abstract: The aim of the present work is to investigate the effect of halloysite nanotubes (HNT) on the mechanical properties of low-density polyethylene composites modified by maleic anhydride-grafted PE (PE-graft-MA). Polyethylene nanocomposites were prepared using an injection molding machine, Arburg Allrounder 320 C 500–170; the HNT content was varied at 0 wt %, 2 wt %, 4 wt % and 6 wt %, and the PE-graft-MA content was varied at 5 wt %. The composites were examined for their ultimate tensile stress, strain at ultim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 37 publications
4
26
0
Order By: Relevance
“…The values of tensile strength decreased due to the weak interaction between the filler and the polymer matrix, which was not strong enough to transfer the stress from HDPE to P3 and MG5 efficiently [22]. This finding is in line with the result reported by Sikora et al (2019) [17]. It is noteworthy that the tensile strength of nanocomposites can be negatively affected by the filler content since the possibility of nanoparticles agglomeration increases with the higher filler concentration [12].…”
Section: Mechanical Properties Analysessupporting
confidence: 87%
See 1 more Smart Citation
“…The values of tensile strength decreased due to the weak interaction between the filler and the polymer matrix, which was not strong enough to transfer the stress from HDPE to P3 and MG5 efficiently [22]. This finding is in line with the result reported by Sikora et al (2019) [17]. It is noteworthy that the tensile strength of nanocomposites can be negatively affected by the filler content since the possibility of nanoparticles agglomeration increases with the higher filler concentration [12].…”
Section: Mechanical Properties Analysessupporting
confidence: 87%
“…Based on the previous findings of several studies, it can be concluded that the influence of nanofiller's type and concentration on the properties of the obtained composites should be evaluated independently for every matrix and type of filler [14][15][16][17]. The present research aims to fabricate two types of alumina PNCs without neither performing any kind of surface treatment/modification nor using coupling agents.…”
Section: Introductionmentioning
confidence: 99%
“…where ∆H m is the melting enthalpy and ∆H 0 m is the melting enthalpy of 100% crystalline PE (293 J/g) [36], and PLA (93 J/g) [60], respectively. In the TPS test specimens the degree of crystallinity was determined for the PE matrix.…”
Section: Research Programme and Methodologymentioning
confidence: 99%
“…DSC measurement results for granulates. The values of T g (below −110 • C) revealed that LDPE [36] was one of the additives, and a polymer that is not biodegradable. The values of T g were approximately at −30 • C as read from the DSC curves plotted for PLA, TPS-C, and TPS-P, and partial to presence of other processing additives in the tested bioplastics.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
See 1 more Smart Citation